2021
DOI: 10.1155/2021/9370758
|View full text |Cite
|
Sign up to set email alerts
|

Governor Vessel Moxibustion Therapy Improves Microbiota Structure in Ankylosing Spondylitis Patients

Abstract: Background. Clinical studies have shown that ankylosing spondylitis (AS) could be significantly improved by Governor Vessel moxibustion (GVM) therapy. Objective. Study whether GVM therapy alleviates the clinical symptoms of AS by modulating intestinal microbiota. Methods. A total of 9 AS patients and 9 paired healthy individuals were enrolled, and GVM therapy was provided to the AS patients. Stool, urine, and saliva samples from the healthy individuals and the AS patients before and after GVM therapy were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…It is the primary representative therapy of warm Yang to remove pathogenic factors . [ 13 ] As the sea of the Yang vessel, the governor vessel can be unified supervision of Yang Qi the whole body and is the key to the coordination of Yin and Yang. [ 14 ] The canicular days are the time when Yang Qi reaches its peak according to TCM theory.…”
Section: Discussionmentioning
confidence: 99%
“…It is the primary representative therapy of warm Yang to remove pathogenic factors . [ 13 ] As the sea of the Yang vessel, the governor vessel can be unified supervision of Yang Qi the whole body and is the key to the coordination of Yin and Yang. [ 14 ] The canicular days are the time when Yang Qi reaches its peak according to TCM theory.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 2 articles were human studies, and 6 were animal studies. The characteristics of the included studies and microbiome modulation results are shown in Tables 1 [13,14] and 2 [15][16][17][18][19][20].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Another study [14] investigated the effectiveness of moxibustion on clinical outcomes and the gut microbiome modulation in patients with AS. After moxibustion, various clinical outcomes including bath AS disease activity index and bath AS function index were significantly improved in the AS patients.…”
Section: Modulation On Microbiome In Human Studiesmentioning
confidence: 99%